2017
DOI: 10.3390/environments5010002
|View full text |Cite
|
Sign up to set email alerts
|

Particle (Soot) Pollution in Port Harcourt Rivers State, Nigeria—Double Air Pollution Burden? Understanding and Tackling Potential Environmental Public Health Impacts

Abstract: Residents of Port Harcourt in Rivers State, Nigeria, and its environs have since the last quarter of 2016 been experiencing adverse environmental impacts of particle (soot) pollution. This “double air pollution burden”—the unresolved prevailing widespread air pollution and the “added” emergence of particle pollution considered an environmental health threat, led to protests against government inaction in some parts of the state. In February 2017, several months following the onset of the pollution, the governm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 54 publications
4
61
1
6
Order By: Relevance
“…(Standards Organization of Nigeria, 2007) Temperature, turbidity, chlorine, dissolved oxygen, magnesium, total coliform, fecal coliform, oil/grease and TPH values were all found to be higher than the national drinking water standard. This finding is corroborated by the research findings of Braide et al (2016) and Ugwoha et al (2017); who reported elevated temperatures in surface and groundwater water samples that were tested. Egwurugwu et al (2013) also reported elevated temperature, dissolved oxygen as well as magnesium levels in water samples obtained from gas flaring areas.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…(Standards Organization of Nigeria, 2007) Temperature, turbidity, chlorine, dissolved oxygen, magnesium, total coliform, fecal coliform, oil/grease and TPH values were all found to be higher than the national drinking water standard. This finding is corroborated by the research findings of Braide et al (2016) and Ugwoha et al (2017); who reported elevated temperatures in surface and groundwater water samples that were tested. Egwurugwu et al (2013) also reported elevated temperature, dissolved oxygen as well as magnesium levels in water samples obtained from gas flaring areas.…”
Section: Discussionsupporting
confidence: 81%
“…Another study identified distortions in water samples gotten from these gas flaring areas as a direct consequences of the flaring activities which are capable of distorting the chemical and biological composition of the drinking water in affected areas. (Ugwoha & Omenogor, 2017) Also notable in this study was that the pH (of some samples), bicarbonate, iron, fluoride and sulphate values of the tested water samples were found to be lower than the national drinking water standards. These findings are similar to the findings of Dami et al (2012) who reported reduced levels of the above stated parameters.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Izloženost ljudi zagađenom vazduhu može dovesti do različitih zdravstvenih efekata, zavisno od vrste zagađenja, koncentracije, trajanja i učestalosti izloženosti i štetnosti zagađujućih materija [1]. Najozbiljnija ekološka pretnja urbanoj populaciji potiče upravo od zagađenja vazduha, s obzirom na to da se povezuje sa tri miliona preranih smrti svake godine [2]. Jedan od značajnih faktora promene kvaliteta vazduha je čađ, koja najčešće nastaje kao posledica nepotpunog sagorevanja fosilnih goriva.…”
Section: Uvodunclassified
“…Jedan od značajnih faktora promene kvaliteta vazduha je čađ, koja najčešće nastaje kao posledica nepotpunog sagorevanja fosilnih goriva. Čađ čine veoma fine čestice koje mogu dospeti u organizam putem inhalacije vazduha u zatvorenom prostoru ili spoljašnjoj sredini, ingestije kontaminirane hrane, kao i kontakta sa kožom [2,3]. Obavezan sastojak zagađenog vazduha urbanih sredina je i sumpor dioksid.…”
Section: Uvodunclassified